Library and Information System in Andhra Pradesh: An Overview - Varalakshmi, R.S.R. (DESIDOC Journal of Library & Information Technology, 2015)
The State of Andhra Pradesh had a long history of library system prior to Indian independence when it was part of Madras Presidency. Over the time significant changes occurred in the library and information system. The present study is an attempt to overview the growth and functioning of academic, public and special library and information systems in the State of Andhra Pradesh. The study has been taken up with six parameters–budget, professional staff, collection, automation, ICT infrastructure and services. The analysis is based on data gathered through questionnaire, phone calls and information available on institutions’ website. The findings indicate lopsided functioning of all types of libraries.